2003
DOI: 10.1007/s11661-003-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural effects on moisture-induced embrittlement of isothermally forged TiAl-based intermetallic alloys

Abstract: By using isothermally forged TiAl-based intermetallic alloys, various microstructures (of ␥ -grain, duplex, dual-phase, and fully lamellar microstructures) were prepared. These TiAl-based intermetallic alloys were tensile tested in vacuum and air as functions of strain rate and temperature to investigate microstructural effects on the moisture-induced embrittlement. All the intermetallic alloys with different microstructures showed different levels of reduced tensile stress (or elongation) in air at room tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the previous study, which used isothermally forged TiAl-based intermetallic alloys with various microstructures [16] and other TiAl-based alloys, [12] the reduction in fracture stress or tensile elongation (i.e., the so-called moisture-induced or hydrogen-induced embrittlement) has been observed at ambient temperatures, when the alloys are deformed in air and hydrogen gas. It has been suggested that the moisture-induced (or hydrogen-induced) embrittlement of many intermetallic alloys, including TiAl, occurs because of both the decomposition of moisture (or hydrogen gas) on the alloy surface (or on the freshly exposed grain boundaries or cleavage planes), and the subsequent microprocesses, such as the permeation of the alloy by atomic hydrogen, or the migration and condensation of atomic hydrogen to the grain boundaries (or lattice planes) in front of a propagating microcrack.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, which used isothermally forged TiAl-based intermetallic alloys with various microstructures [16] and other TiAl-based alloys, [12] the reduction in fracture stress or tensile elongation (i.e., the so-called moisture-induced or hydrogen-induced embrittlement) has been observed at ambient temperatures, when the alloys are deformed in air and hydrogen gas. It has been suggested that the moisture-induced (or hydrogen-induced) embrittlement of many intermetallic alloys, including TiAl, occurs because of both the decomposition of moisture (or hydrogen gas) on the alloy surface (or on the freshly exposed grain boundaries or cleavage planes), and the subsequent microprocesses, such as the permeation of the alloy by atomic hydrogen, or the migration and condensation of atomic hydrogen to the grain boundaries (or lattice planes) in front of a propagating microcrack.…”
Section: Discussionmentioning
confidence: 99%
“…[16] For example, the reduced tensile fracture stress observed in the Ti-44Al-7Nb-0.2C alloy (with a fully lamellar microstructure) did not recover up to the highest temperature tested, while that observed in the Ti-42Al-5Mn alloy (with a duplex microstructure (of ␥ and lamellar (␥/␣ 2 ) grains) mixed with an isolated ␤ phase) almost fully recovered at 1050 K. It is speculated that high-temperature environmental embrittlement cannot operate when extensive plastic deformation, promoted by the climb-and-glide motion of dislocations, occurs, the flow strength and, in turn, rendering the hydrogen ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that the hydrogen embrittlement resistance of single γ structure is best, while duplex is the worst. For the fully lamellar microstructure, the effect of hydrogen embrittlement resistance increases with the decrease of lamellar spacing [ 21 ]. In addition to the influence of microstructure, alloying elements also play a positive role in resisting environmental embrittlement [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Moisture-induced embrittlement of L1 2 -type intermetallic alloys has been considered to be caused by hydrogen released from moisture in air, 13) and to involve micro-processes such as generation of hydrogen by decomposition of moisture on the alloy surface, absorption of hydrogen into the alloy, migration and condensation of hydrogen at grain boundaries in front of a propagating micro crack introduced from alloy surface during deformation. [14][15][16] Eventually, grain boundary cohesion and associated plastic work are reduced by stress field arising in front of a propagating micro crack due to hydrogen condensation, and consequently intergranular fracture occurs, resulting in low ductility.…”
Section: Introductionmentioning
confidence: 99%